PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS WEB PADA MATA PELAJARAN KKPI SMKN 3 PADANG - Meta, Monanda Rio (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
This research inteded to develop web-based instructional instrument for KKPI subject at SMK Negeri 3 Padang and find out its validity, practicality and effectivity of the instructional instrument that had been developed. This research was a Research and Development (R and D) method, and 4D (Four D) model of development that consist of four steps: define, design, develop and disseminate. The data used was prime data wich was given from expert, teachers, and students. The results of this development research was: (1) The validity of RPP of this instructional instrument was very good, the validity of media is good and its e-learning module validity considered good (2) The practicality of RPP of instructional instrument by teacherâs respond was considered very good, and judging from students the module considered very practical (3)The effectivity of this Instructional Instrument is good to improve learning outcomes of the students. Based on those results concluded that this Web-Based Instructional Instrument is valid, practical, and effective to be used as instructional instrument on KKPI subject.